Twitter/X as a tool for latin American Journalists: usage patterns and personal branding development - Aguilar Marrugo, Génesis Sofía (2025)
This research analyses how Latin American journalists use Twitter/X features (Threads, Polls, Spaces, Live, Lists, and Topics) in their journalistic practice and in developing their brand. Through a mixed-method survey conducted between June and September 2023, 165 valid responses were collected, allowing for the identification of usage patterns and perceptions. The results indicate that, despite the advantages offered by the platform’s features, their adoption in journalistic practice remains low. Although journalists recognize the potential of these tools, their use is often sporadic or nonexistent. In contrast, there is a strong interest in strengthening professional identity and building a solid personal brand on Twitter/X prioritize publishing workrelated content over personal aspects, implementing visibility and positioning strategies. Journalists prioritize publishing work-related content over personal aspects, implementing visibility and positioning strategies to achieve this. These findings suggest that Twitter/X is perceived more as a channel for journalistic dissemination and selfpromotion than as a space for innovation in professional practice.